Marker-assisted forward and backcross breeding for improvement of elite Indian rice variety Naveen for multiple biotic and abiotic stress tolerance - Janaki Ramayya, Perumalla; Vinukonda, Vishnu Prasanth; Singh, Uma Maheshwar; Alam, Shamshad; Venkateshwarlu, Challa; Vipparla, Abhilash Kumar; Dixit, Shilpi; Yadav, Shailesh; Abbai, Ragavendran; Badri, Jyothi; T., Ram; Phani Padmakumari, Ayyagari; et al. (Public Library of Science, 2021)
The elite Indian rice variety, Naveen is highly susceptible to major biotic and abiotic stresses such as blast, bacterial blight (BB), gall midge (GM) and drought which limit its productivity in rainfed areas. In the present study, a combined approach of marker-assisted forward (MAFB) and back cross (MABC) breeding was followed to introgress three major genes, viz., Pi9 for blast, Xa21 for bacterial blight (BB), and Gm8 for gall midge (GM) and three major QTLs, viz., qDTY1.1, qDTY2.2 and qDTY4.1 conferring increased yield under drought in the background of Naveen. At each stage of advancement, gene-based/linked markers were used for the foreground selection of biotic and abiotic stress tolerant genes/QTLs. Intensive phenotype-based selections were performed in the field for identification of lines with high level of resistance against blast, BB, GM and drought tolerance without yield penalty under non-stress situation. A set of 8 MAFB lines and 12 MABC lines with 3 to 6 genes/QTLs and possessing resistance/tolerance against biotic stresses and reproductive stage drought stress with better yield performance compared to Naveen were developed. Lines developed through combined MAFB and MABC performed better than lines developed only through MAFB. This study exemplifies the utility of the combined approach of marker-assisted forward and backcrosses breeding for targeted improvement of multiple biotic and abiotic stress resistance in the background of popular mega varieties.